Environmental impact on electric vehicle: A cradle-to-cradle approach for various vehicle technologies toward sustainable transportation - Idris, Muhammad; Garniwa, Iwa; Soesilo, Tri Edhi Budhi; Utomo, Suyud Warno (International Journal of Renewable Energy Development, 2026)
The transition to sustainable transportation is critical to global efforts to mitigate climate change and reduce environmental degradation. Life cycle assessment (LCA) provides a comprehensive framework for evaluating the environmental impacts of various vehicle technologies throughout their entire life cycle. Numerous studies have applied cradle-to-gate, cradle-to-wheel, and cradle-to-grave approaches. However, increasing material waste from vehicles and batteries is expected to become a significant environmental challenge due to intensive mining and resource extraction activities. To address this issue, the cradle-to-cradle approach is proposed to mitigate environmental impacts during the end-of-life phase through material recycling and recovery. This study examines manufacturing, operational, and end-of-life phases across various vehicle technologies. Unlike traditional cradle-to-grave assessments, the cradle-to-cradle approach promotes resource circularity by integrating material reuse and recycling into the evaluation process, thereby minimizing waste and optimizing resource efficiency. The analysis identifies critical indicators, including energy consumption, air quality, and greenhouse gas (GHG) emissions. Although electric vehicles (EVs) significantly reduce operational emissions, they present challenges related to battery material extraction and end-of-life management. By incorporating cradle-to-cradle principles, this study highlights strategies to enhance material recovery and reusability, particularly for battery components and lightweight materials. Furthermore, this research underscores the importance of adopting renewable energy sources and circular economy principles in the transportation sector to achieve sustainability goals. Policy recommendations include strengthening recycling infrastructure, incentivizing eco-friendly vehicle design, and fostering cross-sector collaboration. The findings contribute to a deeper understanding of sustainable vehicle technology pathways and provide a framework for reducing environmental impacts while meeting growing transportation demands.